2011
DOI: 10.3325/cmj.2011.52.171
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MAGE-A and NY-ESO-1 cancer/testis antigens in medullary breast cancer: a retrospective immunohistochemical study

Abstract: AimTo immunohistochemically evaluate the expression of MAGE-A1, MAGE-A, and NY-ESO-1 cancer/testis (C/T) tumor antigens in medullary breast cancer (MBC) tumor samples and to analyze it in relation to the clinicopathological features.MethodsThis retrospective study included samples from 49 patients: 40 with typical MBC and 9 with atypical MBC. Tumor specimens were obtained from patients operated on in the University Hospital for Tumors and the Sisters of Mercy University Hospital, Zagreb, Croatia, from 1999 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Ademuyiwa et al [1] reported that NY-ESO-1 expression was associated with better progression-free survival in TNBC, though it was not statistically significant. On the contrary, Matkovic et al [40] reported that NY-ESO-1 expression was associated with poor overall survival in medullary breast cancer; however, the study population was relatively small (49 patients) and included HR-positive patients. Both studies did not analyze the prognostic value of NY-ESO-1 expression according to the adjuvant chemotherapy status.…”
Section: Discussionmentioning
confidence: 98%
“…Ademuyiwa et al [1] reported that NY-ESO-1 expression was associated with better progression-free survival in TNBC, though it was not statistically significant. On the contrary, Matkovic et al [40] reported that NY-ESO-1 expression was associated with poor overall survival in medullary breast cancer; however, the study population was relatively small (49 patients) and included HR-positive patients. Both studies did not analyze the prognostic value of NY-ESO-1 expression according to the adjuvant chemotherapy status.…”
Section: Discussionmentioning
confidence: 98%
“…CTAs have already been analyzed in different types of malignancies, including carcinomas of the liver, pancreas, bladder and the breast . CTA expression in lung cancer, medullary breast and urothelial carcinoma has also been found to impact patients' OS …”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] CTA expression in lung cancer, medullary breast and urothelial carcinoma has also been found to impact patients' OS. [33][34][35] In HNSCC, only two studies have analyzed protein expression of CTA, both with limited patient numbers and only one primary site included. 18,19 The second study was performed by Campos Montoro et al 19 and analyzed 23 oral squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with other CT antigens, MAGE-C1/CT7 expression was found only in 18% (22 of 124) of invasive breast cancer patients [31]. Recently, MAGE-A1, MAGE-A, and NY-ESO-1 protein expression was reported only in 33% (16/49), 33% (16/49), and 22% (11/49) of breast cancer patients, respectively by IHC analysis [32]. In addition, the three other CT antigens –GAGE, SAGE1 and Nuclear RNA export factor 2 (NXF2), were infrequently or rarely expressed, only in 3.5%, 2.2% and 1.8% of the breast cancer patients, respectively [33].…”
Section: Discussionmentioning
confidence: 99%